1999
DOI: 10.1111/j.1600-0447.1999.tb05379.x
|View full text |Cite
|
Sign up to set email alerts
|

Family burden and coping strategies in schizophrenia: are key relatives really different to other relatives?

Abstract: Subjective and objective burden, psychiatric symptoms and coping strategies in a sample of 90 key relatives and other relatives of patients with schizophrenia, living in two European countries, were explored by means of well-validated questionnaires. The levels of burden on key relatives did not differ significantly from those on other relatives. Moreover, the risk of developing psychiatric symptoms was similar in the two subject groups at both centres. Significant correlations were found between key relatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 15 publications
3
43
0
7
Order By: Relevance
“…Only one third of the Indian sample and one fifth of the White sample experienced mild distress measured with the GHQ. This proportion of distressed Indian parents was lower than some caregiver burden studies in mental illness (Bibou-Nakou et al, 1997) and comparable with others (Magliano et al, 1999).…”
Section: Levels Of Burden and Psychiatric Morbidity In Parentsmentioning
confidence: 71%
“…Only one third of the Indian sample and one fifth of the White sample experienced mild distress measured with the GHQ. This proportion of distressed Indian parents was lower than some caregiver burden studies in mental illness (Bibou-Nakou et al, 1997) and comparable with others (Magliano et al, 1999).…”
Section: Levels Of Burden and Psychiatric Morbidity In Parentsmentioning
confidence: 71%
“…However, it is considered to be similar to 'Positive communication' in the FCQ, which is a problem-focused strategy. A previous research found that 'Positive communication' is one of the commonly-used strategies among main and side caregivers (19). This 'Caring for patient' strategy involves giving more attention and speaking in good ways to the patients during stressful times, unlike other strategies which involve actions or activities that focus more on the caregivers themselves.…”
Section: Discussionmentioning
confidence: 99%
“…For each patient, one or more key-relatives could be recruited. Key-relatives were defined as those spending the highest number of hours in contact with the patient during the last year (Magliano et al, 1999).…”
Section: Recruitmentmentioning
confidence: 99%